Standardization of Grafting Time of Mandarin (Citrus reticulata Blanco) in Central Mid Hill of Nepal. Issue 1 (1st January 2021) - Bhandari, N.; Basnet, M.; Khanal, S.
ABSTRACT: An investigation was carried out to study the performance of mandarin grafts during 2017–18 at Banepa, Kavre to standardize suitable grafting time for two mandarin varieties. The experiment was conducted in two factorial Completely Randomized Design (CRD) with 10 treatments and three replications. The treatments consisted of combinations of five grafting dates (25 th November, 10 th December, 25 th December, 10 th January and 25 th January) and two mandarin varieties (Dhankuta Local and Ota Ponkan). Scion collected from mother plants of selected varieties were grafted onto a trifoliate orange rootstock by side veneer method in the screen house. The results showed that grafting dates significantly affect the graft success and subsequent growth of grafted sapling of mandarin varieties. The highest graft success (100%) was observed on the grafts prepared in January. The sapling height (47.58 ± 1.93 cm), leaf area (32.74 ± 2.98 cm 2 ), number of primary branches per sapling (3.16 ± 0.20) and increase in diameter above union (17.78 ± 1.47%) were recorded maximum on the grafts prepared on 25 th January while the number of leaves per sapling (26.81 ± 1.84) was found superior for 10 th January grafted sapling. Most of the important parameters viz., graft success percent, sapling height and leaf area were found non-significant for varieties but the number of leaves per sapling (23.99 ± 1.51), number of primary branches per sapling (2.72 ± 0.21), increase in diameter above union (16.24 ± 0.88%) and at union (13.72 ± 1.54%) was found maximum for Ota Ponkan. Therefore, the study revealed that late January was the most suitable time of grafting for both varieties of mandarin under Kavre, Nepal conditions.